Analysis of Product Strategy and Design in Establishing a Local Merchandise Business Based on Yogyakarta Batik Cultural Identity - Nurul Jennah; Abdur Rohman (Penerbit Hellow Pustaka, 2026)
This study aims to analyze the development of merchandise products inspired by Batik Yogyakarta, which continue to reflect local cultural values while also possessing strong visual and market appeal in the modern era. Batik Yogyakarta is recognized as a cultural heritage rich in philosophy and historical significance, making it highly potential for development as a creative product, such as merchandise. This study focuses on three main aspects: strategies for product development, design approaches that align with traditional values while remaining responsive to contemporary trends, and identifying technical and operational challenges that arise during the merchandise production process. The research adopts a literature review method with a qualitative descriptive approach, involving an analysis of various scientific references, articles, and journals relevant to the development of culture-based products.